(untitled) (American Journal of Islam and Society, 2013)
On June 24-July 3, 2013, the International Institute of Islamic Thought held its annual Summer Institute for Scholars. Given the number of presentations, only a few of them will be mentioned here. In his welcoming remarks, Abdul Aziz Sachedina (George Mason University) spoke eloquently about how change has to come from within, how politics still dominates values, and how the Qur’an and Sunnah are being read not for inspiration, but for putting down opposition and dissenters. The Arab Spring represents a challenge to undertake such an internal reform. Unfortunately, he said, cyberspace contains no serious conversation in this regard, just hostility and animosity, which only damages Muslims. He called for leaders to “moralize” the entire issue in order to achieve co-existence, mainly between Shi‘is and Sunnis, and wondered if the reformers could deal with this and other issues. John Voll (Georgetown University), who delivered the keynote address, “Pop-politics and Elections: Islam and Democracy after the Arab Spring,” raised the question as to whether the Arab Spring makes any difference, given that reform movements have been going on in the Muslim world since 1880. Are we, he asked, “looking at something moving forward/different, or just rehashing the same old arguments?” He opined that a new vocabulary is needed and that people have to move beyond “interfaith,” “tolerance,” and interreligious dialogue and speak to each other about “shared interests.” He then discussed earlier Muslim reform movements and how their goals have changed over the years. Yahya Michot (Hartford University) presented a special lecture entitled “Taymiyyan Thoughts for a Temperate Arab Summer.” He pointed out how different groups (e.g., those groups responsible for assassinating Sadat, the Algerian civil war, and 9/11) took Ibn Taymiyyah’s anti-Mongol fatwas out of context to justify their actions. Thus they ignored the underlying issues: The supposedly “Muslim” Mongols were still massacring Muslims; ...